Studi Tingkat Kerusakan Garis Pantai Dan Prioritas Penanganan di SWPP Minahasa - Jasin, Muhammad Ihsan (JURNAL ILMIAH MEDIA ENGINEERING, 2011)
Study of coastal damage level is one way in determining the quality of coastal territorial units, whether classified as damaged or good. Study of the calculation process that occurs in each location of the beach, followed by calculation of the score of each location and determine the level of damage based on the total score obtained from each location of the beach. The amount of damage the coastal territory can be classified in class so Very Preferred, Very Preferred, Preferred and Less Preferred.The result of the assessment of damages in Minahasa SWPP classified into 4 categories of damage that is 4 level beach classified locations Extremely Serious, 3 beach sites have high levels of damage Very Serious and 7 locations coast to the level of damage Serious and 2 locations with slightlydamaged.Keywords: damage level, coastal territorial units